Multimedia for Learning Science in Elementary School - Nur Cholid (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This study aimed to: 1) develop multimedia learning science can be used to solve students' learning problems, especially lack of student learning resources, and 2) test the feasibility of multimedia learning products developed for elementary science learning. This research is a development involving 50 respondents, consisting of 6 students for one-on-one test, 12 students for the test group, and 32 for field trials. Before the product tested and validated by experts material media experts assessed by a scale of 1-5. Aspects of assessment include material aspects, aspects of learning and media aspects. Data were analyzed by descriptive quantitative. The results showed: 1) the development of multimedia learning science has been conducted with media development procedures, including preliminary research, learning analysis, production / media development, and revision, while the evaluation of multimedia learning science for elementary / MI has been developed in accordance with the evaluation procedures media development. 2) the results of the validation by experts and media materials show that multimedia learning science has a good quality of learning (with a value of 4.16), good quality material with a value of 4.20) and a media display quality is very good (with a value of 4.30) and good quality media programming (with a value of 4.13). Average Field Trial results show that multimedia learning science teaching quality is very good (with a value of 4.63), and the quality of the material is excellent (with a value of 4.66) and the excellent quality of the media (with a value of, 4, 68). These results indicate that the developed multimedia science learning be used as a medium of learning and learning resources. Keywords: Multimedia Development, Learning Science